1961
DOI: 10.1063/1.1777047
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on SnS

Abstract: The p, T, x diagram of the Sn-S system was determined especially in the region of the compound SnS. The pressure of S2 in equilibrium with SnS and a liquid phase was found to extend over several decades up to 25-mm Hg at the ``Sn-rich'' side, whereas at the ``S-rich'' side the S2 pressures in equilibrium with solid SnS and a liquid phase lie between 25-mm Hg and 100-mm Hg. It was shown that the existence region of solid SnS very probably lies entirely at the excess sulfur side. The hole mobility in a plane per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
150
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(172 citation statements)
references
References 6 publications
18
150
3
1
Order By: Relevance
“…Albers et al reported the use of Sb as a dopant that lowers the hole concentration of SnS to be less than 10 14 cm -3 . 13 Nonetheless, the specific Sb concentration and detailed studies of its effect on the electrical properties of SnS were not reported. By increasing the Sb concentration further, it might be possible to convert SnS to an n-type semiconductor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Albers et al reported the use of Sb as a dopant that lowers the hole concentration of SnS to be less than 10 14 cm -3 . 13 Nonetheless, the specific Sb concentration and detailed studies of its effect on the electrical properties of SnS were not reported. By increasing the Sb concentration further, it might be possible to convert SnS to an n-type semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…12 This approach requires SnS to have a low carrier concentration on the order of 10 13 cm -3 , which is lower than typical undoped SnS values of 10 15 -10 18 cm -3 . 3,4,6,13 Therefore, the ability to control carrier concentration and conduction type of SnS could improve SnS-based thin film solar cells and, in general, could broaden the utility of SnS as an optoelectronic semiconductor outside the field of photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tin (II) sulfide (SnS) is one such material, which has high potential in device fabrication due to its non-toxicity and easy availability of the constituent materials. It is a IV-VI layered compound semiconductor with distorted NaCl type orthorhombic crystal structure [3]. Due to its interesting structural, optical and electrical properties, SnS has become an important material for optoelectronics and photovoltaics [4][5][6][7] with many promising technological applications [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic structure and structural calculations of SnS were deduced from photoelectron spectra by Ettema et al [13]. Optoelectronic properties suitable for the device fabrication were also reported by several groups [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%